Expression of the cytokinesis regulator PRC1 results in p53-pathway activation in A549 cells but does not directly regulate gene expression in the nucleus. Issue 4 (16th February 2023) - Hanselmann, Steffen; Gertzmann, Dörthe; Shin, Woo Jin; Ade, Carsten P.; Gaubatz, Stefan
ABSTRACT: Protein regulator of cytokinesis 1 (PRC1) is a microtubule-binding protein with essential roles in mitosis and cytokinesis. PRC1 is frequently overexpressed in cancer cells where it could contribute to chromosomal instability. Due to its nuclear localization in interphase, it has been speculated that PRC1 has additional functions that are involved in its pro-tumorigenic functions. In this study we investigated the potential nuclear functions of PRC1 in a lung cancer cell line. Genome wide expression profiling by RNA sequencing revealed that the expression of PRC1 results in activation of the p53 pathway and inhibition of the pro-proliferative E2F-dependent gene expression. A mutant of PRC1 that is unable to enter into the nucleus regulated the same gene sets as wildtype PRC1, suggesting that PRC1 has no nuclear-exclusive functions in A549 cells. Instead, induction of p53 by PRC1 correlates with multinucleation and depends on the localization of PRC1 to the midbody, suggesting that the induction of p53 is a consequence of overexpressed PRC1 to interfere with the normal function of PRC1 during cytokinesis. Activation of p53 by PRC1 results in cellular senescence but not in apoptosis. In conclusion, while PRC1 is frequently overexpressed in many cancers, the p53 pathways may initially protect cancer cells from the negative effects of PRC1 overexpression on cytokinesis. Because depletion of PRC1 also results in p53-pathway activation and senescence, levels of PRC1 need to be tightly regulated to allow unperturbed proliferation. Targeting the expression or function of PRC1 could create a therapeutic vulnerability for the treatment of cancer.